Coupling in ATP synthesis: Test of thermodynamic consistency and formulation in terms of the principle of least action - Nath, Sunil (Chemical physics letters, 2019)
[Display omitted] •The coupled processes of ATP synthesis operate at optimal thermodynamic efficiency.•The state is compatible with maximum dissipation under the imposed constraints.•These results are consistent with nonequilibrium thermodynamics.•The total action for a selected final state is a maximum compatible with the constraints.•The system evolves to a minimum unit action of 1.4 × 10−3 J s natom O−1 mg protein−1. The coupled nonequilibrium processes of ATP synthesis in oxidative phosphorylation (OX PHOS) are tuned such that the system operates at optimal thermodynamic efficiency, η. This state is compatible with maximum free energy dissipation, Φ under the imposed constraints. These results are shown to be consistent with nonequilibrium thermodynamics. Analysis of experimental data on rat liver mitochondria with succinate as substrate demonstrates that the total action of the system for a selected final state is a maximum compatible with the constraints, and that the system evolves with time to a minimum average unit action of 1.4 × 10−3 J s natom O−1 mg protein−1. This value of least average unit action corresponds to the highest efficiency of the system, compatible with the constraints to which the system is subject.